Genome-wide identification and expression analysis of AUX/LAX family genes in Chinese hickory (Carya cathayensis Sarg.) Under various abiotic stresses and grafting - Yang, Ying; Wang, Jiayan; Xu, Yan; Abbas, Farhat; Xu, Dongbin; Tao, Shenchen; Xie, Xiaoting; Song, Feng; Huang, Qiaoyu; Sharma, Anket; Zheng, Luqing; Yan, Daoliang; et al. (Frontiers in Plant Science, 2023)
Auxin is essential for regulating plant growth and development as well as the response of plants to abiotic stresses. AUX/LAX proteins are auxin influx transporters belonging to the amino acid permease family of proton-driven transporters, and are involved in the transport of indole-3-acetic acid (IAA). However, how AUX/LAX genes respond to abiotic stresses in Chinese hickory is less studied. For the first time identification, structural characteristics as well as gene expression analysis of the AUX/LAX gene family in Chinese hickory were conducted by using techniques of gene cloning and real-time fluorescent quantitative PCR. Eight CcAUX/LAXs were identified in Chinese hickory, all of which had the conserved structural characteristics of AUX/LAXs. CcAUX/LAXs were most closely related to their homologous proteins in Populus trichocarpa , which was in consistence with their common taxonomic character of woody trees. CcAUX/LAXs exhibited different expression profiles in different tissues, indicating their varying roles during growth and development. A number of light-, hormone-, and abiotic stress responsive cis-acting regulatory elements were detected on the promoters of CcAUX/LAX genes. CcAUX/LAX genes responded differently to drought and salt stress treatments to varying degrees. Furthermore, CcAUX/LAX genes exhibited complex expression changes during Chinese hickory grafting. These findings not only provide a valuable resource for further functional validation of CcAUX/LAXs, but also contribute to a better understanding of their potential regulatory functions during grafting and abiotic stress treatments in Chinese hickory.